Distribution of Different Forms of Manganese and Iron in The Soils of Extremely Arid Part of Western Rajasthan - Joshi, D C; Dhir, R P (Annals of Arid Zone, 2016)
Different forms of manganese and iron in the soils of extremely arid part of western Rajasthan have been reported. Total manganese and iron contents of the soils were slightly higher in south western sandy plain. Except the playa soils, which contained lower amounts of reducible and active manganese, all the sandy plain soils generally contained these forms of manganese comparable to the adjoining arid zone soils but were quite low when corr.- pared with the similar soils of Punjab and Haryana. The significant correlations between different forms of manganese and also with pH and CaC03 and non significant correlations between forms of iron and with the soil parameters indicated that availability of these two nutrients was not governed by the similar soil characteristics.